(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
This paper provides a comprehensive study of the documentary and graphic transmission of the so-called Vaso de Torres (Jaén, Spain) with an Iberian inscription. We focus on the authors who have studied or reproduced the vase from the 17th to the late 19th century. We pay also special attention to the textual transmission of the original testimony by the Marquis de la Aula (1623). Finally, we specifically review the elements that raise suspicions about the authenticity of the vase housed in the Louvre Museum (Paris).